Short Stature in Chronic Kidney Disease Treated with Growth Hormone and an Aromatase Inhibitor - Susan R. Mendley; Fotios Spyropoulos; Debra R. Counts (Hindawi Limited, 2015)
We describe an alternative strategy for management of severe growth failure in a 14-year-old child who presented with advanced chronic kidney disease close to puberty. The patient was initially treated with growth hormone for a year until kidney transplantation, followed immediately by a year-long course of an aromatase inhibitor, anastrozole, to prevent epiphyseal fusion and prolong the period of linear growth. Outcome was excellent, with successful transplant and anticipated complete correction of height deficit. This strategy may be appropriate for children with chronic kidney disease and short stature who are in puberty.